2013
DOI: 10.1007/s00125-012-2822-8
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiotrophin 1 protects beta cells from apoptosis and prevents streptozotocin-induced diabetes in a mouse model

Abstract: Aims/hypothesis Cardiotrophin 1 (CT-1) is a recently described cytokine originally isolated from the heart where it has been shown to play an important role in apoptotic protection of cardiomyocytes and heart hypertrophy. Its beneficial properties have also been described in other organs such as liver and neuromuscular tissue. In the present study, we investigated whether CT-1 can confer protection against pro-apoptotic stimuli in pancreatic beta cells, and its role in insulin secretion and diabetes developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
1
21
1
Order By: Relevance
“…An interesting finding of our group is that the glucose-lowering properties of CT-1 are also observed in mice with streptozotocin (STZ)-induced insulin deficiency, demonstrating an insulin-independent effect of CT-1 on glucose homeostasis [52]. In line with this, the study of Jimé nez-Gonzá lez et al [107] found that CT-1 has a protective effect from apoptosis in MIN6B1 cells and murine islets, and that CT-1 enhances glucose-stimulated insulin secretion in MIN6B1 cells. Studies in vitro and in vivo support the insulin-sensitizing effect of CT-1 in muscle [52].…”
Section: Energy Homeostasis and Intermediate Metabolismmentioning
confidence: 53%
“…An interesting finding of our group is that the glucose-lowering properties of CT-1 are also observed in mice with streptozotocin (STZ)-induced insulin deficiency, demonstrating an insulin-independent effect of CT-1 on glucose homeostasis [52]. In line with this, the study of Jimé nez-Gonzá lez et al [107] found that CT-1 has a protective effect from apoptosis in MIN6B1 cells and murine islets, and that CT-1 enhances glucose-stimulated insulin secretion in MIN6B1 cells. Studies in vitro and in vivo support the insulin-sensitizing effect of CT-1 in muscle [52].…”
Section: Energy Homeostasis and Intermediate Metabolismmentioning
confidence: 53%
“…These data give a solid rationale to continue multiple autoantibody screening among young Sardinians. It could identify individuals potentially eligible for enrolment in clinical trials aimed at reducing the risk of progression from islet autoimmunity towards clinical T1DM [38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…Beside regenerative and anti-apoptotic functions in several tissues, e.g. motoneurons and hepatocytes [7], [8], in a recent study, CT-1 was reported to protect beta cells from apoptosis and to enhance glucose-stimulated insulin secretion, and additionally, to prevent streptozotocin-induced diabetes in a mouse model [9].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, and because of its high expression in tissues that play a pivotal role in the pathogenesis of type 2 diabetes like beta-cells, skeletal muscle and liver [6], [8], [9], the CT-1 gene ( CTF1) would be a promising candidate to associate with diabetes, insulin secretion and insulin sensitivity. Thus, we asked whether genetic variation within or near CTF1 has an impact on insulin secretion and insulin sensitivity in humans.…”
Section: Introductionmentioning
confidence: 99%